Influence of breakup on elastic and α-production channels in the 6Li+ 116Sn reaction *One of the authors (SM) would like to thank DAE-BRNS for financial assistance through a major research project. This work is supported by National Natural Science Foundation of China (U1432247, 11575256, U1632138, 11605253) and China Postdoctoral Science Foundation (2016M602906). (October 2017) - Patel, D.; Mukherjee, S.; Deshmukh, N.; Lubian, J.; Wang 王, Jian-Song 建松; Correa, T.; Nayak, B. K.; Yang 杨, Yan-Yun 彦云; Ma 马, Wei-Hu 维虎; Biswas, D. C.; Gupta, Y. K.; Santra, S.; et al.
Abstract: The effects of breakup reactions on elastic and α-production channels for the 6 Li+ 116 Sn system have been investigated at energies below and near the Coulomb barrier. The angular distributions of α-particle production differential cross sections have been obtained at several projectile energies between 22 and 40 MeV. The measured breakup α-particle differential cross sections and elastic scattering angular distributions have been compared with the predictions of continuum-discretized coupled channels (CDCC) calculations. The influence of breakup coupling has also been investigated by extracting dynamic polarization potentials (DPP) from the CDCC calculations. From the predictions of CDCC calculations the relative importance of the nuclear, Coulomb, and total breakup contributions have also been investigated. The nuclear breakup couplings are observed to play an important role in comparison to the Coulomb breakup for the direct breakup mechanisms associated in the reaction of 6 Li projectile with 116 Sn target nuclei. The influence of strong nuclear breakup coupling exhibits suppression in the Coulomb-nuclear interference peak. The direct breakup cross sections from the CDCC calculations under-predict the measured α-particle differential cross sections at all energies. This suggests that the measured α particles may also have contributions from other possible breakup reaction channels.